A companion to Julian the Apostate
1 online resource.
Keywords: Few Roman emperors enjoy such fame as Flavius Claudius Iulianus – although he was sole ruler of the Roman Empire for only eighteen months (361-363). Since his early death he has been known as Julian the Apostate – the nephew of Constantine the Great who in vain tried to reverse the transformation of the Imperium Romanum into a Christian Empire. This companion synthesizes research on Julian conducted in many languages over the last decades and develops new perspectives. The authors scrutinize the voluminous and variegated sources for Julian's life and rule and reflect on the perceptions of modern research. Since Julian is the subject of scholarly discussion in various fields, this companion offers an interdisciplinary dialogue in which experts from many countries participate. Contributors are Bruno Bleckmann, Scott Bradbury, Peter Heather, Arnaldo Marcone, Neil McLynn, Hans-Günther Nesselrath, Stefan Rebenich, Christoph Riedweg, Sebastian Schmidt-Hofner, Peter van Nuffelen, Konrad Vössing, Hans-Ulrich Wiemer.